The Role of Commerce in the Main Urban Area of Abruzzo: an Intra-Urban Reading - Fabrizio Ferrari; Silvia Iacuone; Silvia Scorrano; Marina Fuschi (Bollettino della Società Geografica Italiana)
Since the 1950s, the urban structure of Abruzzo has gradually polarized on the area of Pescara-Chieti, as the expression of a series of location and settlement advantages. There, the trade sector, favoured by a period of expansion of large-scale commercial distribution, represented a powerful vehicle for territorial convergence and cohesion, contributing to the progressive process of marginalization of urban proximity trade. The aim of this work is to go beyond the opposition between suburban shopping center/central urban trade and to propose an interpretation at intra-urban scale that starts from peripheral neighbourhoods and peculiar spaces: They are able, in some cases, to better represent urban identity, but, above all, to provide a favourable observation point from which to promote a balanced and sustainable reorganization of the city.